Visceral Leishmaniasis with Endobronchial Involvement in an Immunocompetent Adult. (26th January 2011) - Kotsifas, Konstantinos; Metaxas, Eugenios; Koutsouvelis, Ioannis; Skoutelis, Athanassios; Kara, Panayiota; Tatsis, George
Abstract : Visceral leishmaniasis is characterized by fever, cachexia, hepatosplenomegaly, pancytopenia, and hypergammaglobulinemia. Cough may be a presenting symptom as well. However, pulmonary involvement is considered rare and mainly described in immunocompromised patients. We describe a case of an immunocompetent adult whose clinical presentation was dominated by cough and hemoptysis. Bronchoscopy revealed a discreet polypoid mucosal endobronchial lesion whose biopsy yielded Leishmania amastigotes within histiocytes. Transbronchial needle biopsy of a right paratracheal lymph node was also positive. Leishmania amastigotes were also found on bone marrow and liver biopsies. Treatment with IV Amphotericin B was successful. In conclusion, cough should not be overlooked as a presenting symptom of visceral leishmaniasis and may be a sign of pulmonary involvement.